Study of Seroprevalence of viral Hepatitis B,C and HIV Inpreoperative Assessment for Urological Surgeries: Studi Seroprevalensi Hepatitis B, C, dan HIV pada Penilaian Praoperasi untuk Bedah Urologi - Abdulla Y. Altimary; Nadia K. Abduljaleel (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Viral hepatitis B, hepatitis C, and human immunodeficiency virus remain major blood-borne infections that pose occupational hazards to healthcare workers, particularly during surgical procedures involving percutaneous exposure. Specific Background: Routine preoperative screening has been adopted in many medical institutions to identify infected patients and reduce transmission risk during operative interventions. Knowledge Gap: Limited local data are available regarding the seroprevalence of hepatitis B, hepatitis C, and HIV among patients scheduled for urological surgery in Basrah Teaching Hospital and the associated medical and behavioral risk factors. Aims: This study assessed the seroprevalence of HBV, HCV, and HIV among preoperative urological patients and identified related risk factors. Results: In this cross-sectional study of 254 patients, overall seroprevalence of either HBV or HCV was 8.7%, with HBV (5.9%) higher than HCV (2.8%), while HIV was not detected. Significant associations were observed with blood transfusion (P=0.046), dental surgical intervention (P=0.003), renal dialysis (P<0.001), family history of dialysis (P=0.005), and tattooing (P=0.040). Lack of vaccination (87%) and prior dental procedures (56.7%) were common risk exposures. Novelty: The study provides updated hospital-based evidence integrating serological screening with detailed evaluation of demographic, medical, and behavioral determinants in a urological surgical population. Implications: Findings support routine preoperative screening and reinforcement of vaccination and infection control strategies to reduce occupational transmission in surgical settings. Keywords: Preoperative Screening, Hepatitis B Virus, Hepatitis C Virus, HIV Infection, Seroprevalence Key Findings Highlights: Overall infection rate reached 8.7% among elective surgical candidates. Transfusion, dialysis exposure, and tattoo history showed statistical association with positive serology. Absence of immunization was highly prevalent within the studied population.